Analisis Faktor Yang Memengaruhi Minat Berkunjung Masyarakat Ke Pos Pembinaan Terpadu Penyakit Tidak Menular Di UPTD Puskesmas Lahusa Kecamatan Lahusa Kabupaten Nias Selatan - Samsidar Duha; Tri Niswati Utami; Achmad Rifai (Jurnal Kesmas Prima Indonesia, 2021)
Non-Communicable Diseases (PTM) is a problem for public health, so efforts to prevent risk factors are needed. This study aims to analyze the factors that influence the interest in visiting the community to an integrated non-communicable disease guidance post at the UPTD Puskesmas Lahusa, Lahusa District, South Nias Regency. This study used a cross sectional study design. The research took place from June to July 2020 with a total sample of 95 people who were obtained using purposive sampling. Survey data were analyzed using the Chi Square test and logistic regression. The results showed that there was an influence of knowledge on the interest in visiting Posbindu PTM, there was an effect of education on the interest in visiting Posbindu PTM, there was an effect of distance on the interest in visiting Posbindu PTM, there was an effect of work on the interest in visiting Posbindu PTM, there was an effect of income on the interest in visiting to Posbindu PTM, there is an effect of family support on interest in visiting Posbindu PTM, there is an effect of support from health workers on interest in visiting Posbindu PTM at UPTD Puskesmas Lahusa, Lahusa District, South Nias Regency. The variable that most influences the interest in visiting Posbindu PTM at the UPTD Lahusa Puskesmas, Lahusa District, South Nias Regency is family support. Suggestions in this study are for the public to increase their knowledge by actively participating in Posbindu PTM to prevent non-communicable diseases. In addition to increasing knowledge, it is hoped that the family will increase their support for family members who take part in the PTM Posbindu by being willing to take them to Posbindu PTM and accompany them